2018
DOI: 10.18632/oncotarget.25167
|View full text |Cite
|
Sign up to set email alerts
|

The novel anti-androgen candidate galeterone targets deubiquitinating enzymes, USP12 and USP46, to control prostate cancer growth and survival

Abstract: Metastatic castration resistant prostate cancer is one of the main causes of male cancer associated deaths worldwide. Development of resistance is inevitable in patients treated with anti-androgen therapies. This highlights a need for novel therapeutic strategies that would be aimed upstream of the androgen receptor (AR). Here we report that the novel small molecule anti-androgen, galeterone targets USP12 and USP46, two highly homologous deubiquitinating enzymes that control the AR-AKT-MDM2-P53 signalling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Galaterone is a new androgen-targeting agent that acts inhibiting CYP17: this agent antagonizes the AR, inducing a degradation of both full-length and AR-V7 [205]. Furthermore, Galaterone targets two homologous deubiquitinating enzymes—USP12 and USP46—which control the AR-AKT-MDM2-P53 signaling pathway [206]. Phase I and II studies with Galatereone (ARMOR 1 and ARMOR2) have shown a decline in PSA levels in 49% of treated patients [207].…”
Section: Most Recurrent Genetic Abnormalities Observed In Prostatementioning
confidence: 99%
“…Galaterone is a new androgen-targeting agent that acts inhibiting CYP17: this agent antagonizes the AR, inducing a degradation of both full-length and AR-V7 [205]. Furthermore, Galaterone targets two homologous deubiquitinating enzymes—USP12 and USP46—which control the AR-AKT-MDM2-P53 signaling pathway [206]. Phase I and II studies with Galatereone (ARMOR 1 and ARMOR2) have shown a decline in PSA levels in 49% of treated patients [207].…”
Section: Most Recurrent Genetic Abnormalities Observed In Prostatementioning
confidence: 99%
“…The E1-UAF1-USP complex is recruited to the viral origin and is necessary for efficient replication of the HPV genome ( 11 14 ). While the UAF1-USP12 and UAF1-USP46 complexes regulate histone deubiquitination ( 15 ) and the cell survival- and growth-promoting Akt pathway ( 16 20 ), the UAF1-USP1 complex is involved in the Fanconi anemia (FA) DNA repair pathway ( 21 ). HPV genome replication depends on the activation of both the ATM and ATR arms of the cellular DNA damage response (DDR) pathway ( 22 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…USP12 has been shown to regulate the ubiquitination level of histone H2A and H2B [23] and to deubiquitinate AR and MDM2, which regulate the p53-MDM2-AR-AKT signaling network. In addition, USP12 promotes cell survival, proliferation, tumorigenesis, and cell cycle progression by upregulating BMI-1, c-Myc, and cyclin D2 [24][25][26][27]. Our multiplex RT-PCR results showed that USP12 expression was increased by DEHP in A2780 cells, and thus, the above-mentioned findings of its influence on cell cycle progression and proliferation suggest that it may induce POF by influencing oocyte maturation.…”
Section: Discussionmentioning
confidence: 52%